Stability in consumer responses to familiar and new chocolates during a period of exposure. (January 2015) - Næs, Tormod; Segtnan, Anne; Granli, Britt Signe; Menichelli, Elena; Hersleth, Margrethe
Highlights: New results on effects of product exposure. Comparison of rating and take-away choice. Comparison of home testing and in hall tests. Comparison of individual differences and average effects. Abstract: The aim of this paper is to study the effects of exposure to different types of chocolate on consumer responses. Three different chocolates were considered, one established market leader and two new chocolates from a product development project. A group of consumers participated two times in a central location test and were exposed to different chocolates over a 4 weeks period between the two occasions. Main focus is on informed liking with the inclusion of brand name. Both average effects and individual differences in consumers' responses are discussed. The main conclusion of this study is that the liking of the established chocolate was similar before and after exposure (with a slight decrease in liking) while the liking went significantly up for one of the new products.